Between friends - Macomber, Debbie (Don Mills, Ont. : MIRA Books, 2002)
Letters, newspaper clippings, diary entries, and school essays tell a story of a friendship spanning more than half a century.
Keywords: Female friendship -- Fiction; Friendship -- Fiction; Domestic fiction